Evolutionary economic geography location of production and the European Union - Jovanović, Miroslav N. 1957- (Routledge, 2009)
This text brings evolutionary economics to bear upon economic geography in a coordinated study of the European Union.
Keywords: Europäische Union; European Union; Economic geography; Evolutionary economics / European Union countries; Industrial location / European Union countries; Geografía económica; Integración económica internacional; Localización industrial; Producción (Teoría económica); Wirtschaft; Wirtschaftsgeografie; Evolutorische Wirtschaft; Multinationales Unternehmen; Regionalpolitik; Marktstruktur; Industrieansiedlung; Standortplanung; Agglomeration -- Wirtschaft; European Union countries / Economic conditions; Europäische Union. Mitgliedsstaaten